Digital Literacy and its Impact on Reading Interest in Prospective Elementary School Teachers - Haeroni, Ranita; Saptono, Bambang; Kawuryan, Sekar Purbarini; Sayekti, Octavian Muning (Universitas Pendidikan Ganesha, 2023)
The rapid development of technology in the 21st century requires that every individual is skilled in using digital devices, including in the world of education. The ease of accessing information through digital media should increase students' interest in reading. This study aims to analyze the effect of digital literacy on students' reading interest. The research method used is quantitative with survey research methods. The population in this study were all 6th semester students. Sampling in this study used a purposive sampling technique that found 44 students in total. The instrument uses a Likert scale type interval questionnaire. Data analysis techniques, namely descriptive test, normality test, linearity test, and research hypothesis testing using a simple linear regression test. The results of this study indicate that digital literacy has a significant influence on students' reading interest. This means that digital literacy has a strong influence on students' reading interest. Digital literacy also has a positive influence on reading interest, which means that the better the student's digital literacy, the better the student's reading interest. This is indicated by the results of the coefficient table which has a significant value of 0.000 < 0.05. So it can be concluded that there is an influence of digital literacy on students' reading interest.